A Positive Psychology perspective on Chinese EFL students' trait emotional intelligence, foreign language enjoyment and EFL learning achievement. Issue 3 (15th March 2020) - Li, Chengchen
ABSTRACT: The influence of (trait) emotional intelligence (TEI) on academic achievement has been documented in literature, while its influence in the specific domain of L2 learning remains underexplored. The link between EI and negative emotions especially anxiety has been studied in different contexts including applied linguistics. However, it remains unknown how EI is related to positive emotions in L2 learning. Underpinned by theories and assumptions of Positive Psychology, the present study examined the complex relationships between 1307 Chinese high school students' TEI, Foreign Language Enjoyment (FLE), and English-as-a-foreign-language (EFL) learning achievement. The following findings were obtained: (1) Most Chinese high school EFL students reported moderate to high levels of TEI, while low to moderate levels of FLE; (2) Small to medium correlations were found among students' TEI, FLE, self-perceived English achievement and actual English achievement; (3) TEI was partially mediated by FLE to influence perceived achievement and actual achievement indirectly. The results were discussed in accordance with previous relevant findings as well as their theoretical and practical implications for L2 teaching and learning.